Strategic leadership for turbulent times - Kriger, Mark; Zhovtobryukh, Yuriy (New York: Palgrave Macmillan, 2016)
In today's organizations, it is no longer the CEO who acts as the sole strategic leader. From single individuals to larger teams and networks, leaders at all levels are infiltrating the formal organizational structure and making strategic leadership an increasingly complex endeavor. In Strategic Leadership for Turbulent Times, Kriger and Zhovtobryukh shrewdly describe the true experiences of what employees encounter as internal and external environments evolve, and how to uphold the personal and organizational values which affect both human and social capital. They examine leadership strategies that are used in real situations and highlight the importance of managerial wisdom for sustainable growth. Finally, they offer advice for strategic leaders on leading effectively in highly turbulent economic, social, technological, and multicultural times.
Part I. Foundations of strategic leadership -- Reimaging strategic leadership -- Generic approaches to strategic leadership: stars, teams, clans, and networks -- Part II. Strategies for dealing with complexity and change -- An overall model of strategic leadership -- Dynamic coalignments and five levels of strategy: playing multidimensional chess -- Part III. Leadership wisdom, inner meaning and creating healthy organizations in the long term -- The role of charismatic, transformational, and transactional leadership -- Strategic leadership wisdom -- Creating truly healthy organizations in the long term -- Part IV. Putting it all together -- Advice for strategic leaders in turbulent times.
Includes bibliographical references (pages 151-158) and index.
Keywords: Business; Leadership; Organization; Planning; Personnel management; Economics -- Sociological aspects; Business; Economics -- Sociological aspects; Leadership; Organization; Personnel management; Planning